The Rosa Parks story - Sacani, Christine; Steele, Elaine Eason; Devers, Pearl; Qualles, Paris; Dash, Julie; Bassett, Angela; James, Peter Francis; Tyson, Cicely; Claessen, David, 1959-; Hallam-Martin, Wendy; Conlan, Joseph; Cheng, Mayling; et al. (2003)
Dramatic biography of Rosa McCauley Parks, who in 1955 created the spark that began the modern Civil Rights Movement
Information from pre-release promotional materials; release date: Jan. 21, 2003
Originally produced for television broadcast in 2001
Special features: Filmmakers' commentary; additional footage; Civil Rights timeline; trailer
Director of photography, David Claessen ; edited by Wendy Hallam-Martin ; music, Joseph Conlan ; production designer, Mayling Cheng
Angela Bassett, Peter Francis James, Cicely Tyson
MPAA rating: Not rated
Keywords: Parks, Rosa, -- 1913-2005; African Americans -- Alabama -- Montgomery -- Biography; Civil rights workers -- Alabama -- Montgomery -- Biography; African Americans -- Civil rights -- Alabama -- Montgomery; Segregation in transportation -- Alabama -- Montgomery -- History -- 20th century; Montgomery (Ala.) -- Race relations; Feature films; Biographical films; Historical films; Video recordings; Biographies